Muddying the waters: the failure of water restoration bureaucracies in Kansas - Becerra, Terrie A. (Kansas State University, 2010)
In the almost 40 years since the passage of the Clean Water Act and 25 years of regulating nonpoint source pollution, and despite countless state and local community projects focused on water quality issues, clean water goals have not been met. To comprehend this failure and understand how water resources are governed and how water quality goals are pursued, I explore how watershed-level governance structures emerged and function in their specific local environment, within the state hierarchy of water governance, and as implementation of state and national policy. To this end, the structure, process, and outcomes of two newly organized and local watershed-level governance structures in Kansas were examined. An actor-oriented political ecology approach informed by environmental governance and watershed management literature was used to guide the study. Attaining water quality goals necessitates recognizing the connections between the political economy of agriculture, the cultural factors acting upon agricultural producers, and the natural, biophysical environment. Thusly, a comparative case study strategy was employed for the overall research design. Documents and interview transcripts were analyzed employing a grounded theory approach for differences and similarities; they were also sorted into topical categories and coded for common themes. The research questions focused on the agency and capacity of local watershed structures to determine the relations regarding water resource use in their watershed. Central questions addressed structure responsiveness to local versus state or national concerns; the underlying interests reflected by community member participation; and the effectiveness of local water-governance in protecting water resources. Governance models that began with holistic, alternative, participatory strategies are evolving into targeted, problem-solution strategies, and what began as watershed management is becoming problem shed management.
Keywords: water; Watershed Restoration and Protection Strategy; Watershed management; Environmental governance; water quality; Agriculture, General (0473); Environmental Sciences (0768); Sociology, General (0626); Sociology, Social Structure and Development (0700)